Mate, Reyes. (2008). Justicia de las víctimas. Terrorismo, memoria, reconciliación. Barcelona: Ánthropos. ISBN: 9788476588642. Número de páginas: 191. - Jaramillo Marín, Jefferson; Pontificia Universidad Javeriana (2011)
null